Private Security in Guatemala:The Pathway to Its Proliferation - Otto Argueta
It has become commonplace to explain the proliferation of private security services as causally determined by crime rates and institutional weakness. By contrast, this paper ar-gues that another explanatory factor needs to be emphasized, especially for post-war so-cieties: continuity and change of social control mechanisms. The paper first presents the current situation with commercial and noncommercial private security services in Guate-mala (private security companies, as well as neighborhood security committees). Against this background, it reconstructs mechanisms and critical junctures by which the Guatema-lan state sourced out policing functions to the private sector during the war, and traces the reinforcement of these mechanisms in the post-war society. It argues that the proliferation of private security services is an outcome of the overlapping of different political processes and sequences. The continuity of social control mechanisms thereby emerges as a stronger explanatory factor for this proliferation, rather than the common justification of high crime rates.public security, private security companies, path dependency, post-war societies, Central America, Guatemala